KEKERASAN DALAM RUMAH TANGGA PEMICU PERCERAIAN (PERSPEKTIF MAHDZAB DAN HUKUM POSITIF DI INDONESIA) - Nasoha, Ahmad Muhammad Mustain; Syarifah, Zahra Amalia; Subiyanto, Euis Marga Lenawati (AL HUKMU: Journal of Islamic Law and Economics, 2024)
The topic examined in the research is related to divorce due to domestic violence. The research uses a normative legal pattern (jurisprudential-normative), which involves the use of legal regulations to analyze legal material. To ensure the data collected is optimal and relevant to the research objectives. This process involves exploring and assessing various scientific books or writings that are relevant to the research topic. Divorce and Domestic Violence (KDRT) according to Islamic Fiqh illustrate the complexity of the relationship between family, law and religion in dealing with household problems. The family is considered a valuable asset that must be protected, but reality shows that not all households are safe from conflict, even domestic violence. In Islam, women are given a high position and their rights are protected, including the right to be supported by their husbands. However, failure to fulfill these obligations is often the cause of economic hardship in dostic environments. This is also outlined in Law no. 23 of 2004, cases of oppression perpetrated against women within the boundaries of the family environment are categorized into 4 classifications.